Physics Learning Problems During The Covid-19 Pandemic - Lala Nurdila; Sardianto Markos Siahaan (Jurnal Pembelajaran Fisika, 2022)
This study aims to describe the problems experienced in studying physics during the Covid-19 pandemic at State High School in Pagaralam City. The method used in this study was descriptive quantitative. The data were collected using questionnaires that was distributed online using google forms which were then analyzed descriptively. The results stated that the average percentage for each indicator of physics learning problems during the Covid-19 pandemic at State High School Pagaralam City in general there were seven aspects of problems experienced by students and four aspects of problems experienced by teachers. The lower the number obtained, the lower the problem and vice versa. The problems of students include: understanding of material, use of applications, processing time, task work, difficulty to concentrate, interaction process, and motivation in learning. Furthermore, the problems experienced by teachers include: internet network, class control, mastery of technology and material delivery.Keywords: Covid-19 Pandemic, Physics learning problemsDOI: http://dx.doi.org/10.23960/jpf.v10.n1.202210